Election Decision Support System Based on the Best Teacher Performance Assessment in State Smp 2 One Roof SAW Method Using STM Hilir - Adhar, Tengku Afan; Sinaga, Bosker; Sulindawaty, Sulindawaty (Information Technology and Science (ITScience), 2020)
The process of teacher performance assessment Effectively, precisely, Objectively, and transparently is the important point in selecting the best teacher assessment based on their performance. This assessment was Carried out in SMP Negeri 2 One Roof STM Hilir to avoid the accusations of Injustice and family relationship with the assessor in the school, both the Headmaster and the teacher selection committee. Therefore, a decision system is needed in selecting the decision. One method is the which can be used in solving the problem of Multiple Criteria Decision Making (MADM) is by using Simple Additive weighting (SAW) method, Because The method concept is so easy to understand, simple, effective computationally and has ability in measuring the relative performance of alternative decisions in mathematical form. In addition, Also the design application used UML (Unified Modeling Language) is implemented a system roomates in the software by using Web Programming and MySQL as its database. Finally, based on the design of this application, it can be seen that the decision system by using SAW method is very effective, fast, computerized and transparent accurately in Determining the teacher performance in SMPN 2 One Roof STM Hilir.